2003
DOI: 10.1021/ac034624+
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Spore Identification via Proteolytic Peptide Mapping with a Miniaturized MALDI TOF Mass Spectrometer

Abstract: An approach is tested here as a rapid screening method for Bacillus spore species employing bacterial peptide analysis with a miniaturized MALDI TOF mass spectrometer. A limited set of tryptic peptides was generated in situ following selective solubilization of the small, acid-soluble protein family (SASP) from spore samples on the MALDI sample holder. To facilitate species identification, a compact database was created comprising masses of the tryptic cleavage products generated in silico from all Bacillus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Thus, it is presently feasible to analyze a single clinical sample in approximately 1.5 hours or less with results similar to those shown here, and with additional informatics work extremely specific genotyping of any given Flavivirus should be possible. Moreover, all the steps in the protocol are amenable to high-throughput automated im- [27][28][29][30] it will soon be possible to take such cultureindependent molecular assays to remote locations to improve greatly the response time for epidemiological and clinical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is presently feasible to analyze a single clinical sample in approximately 1.5 hours or less with results similar to those shown here, and with additional informatics work extremely specific genotyping of any given Flavivirus should be possible. Moreover, all the steps in the protocol are amenable to high-throughput automated im- [27][28][29][30] it will soon be possible to take such cultureindependent molecular assays to remote locations to improve greatly the response time for epidemiological and clinical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…These peptide databases can be interrogated to provide identifications of microorganisms by algorithms analogous to those developed to search protein databases for suites of protein mass matches. 80,81 This strategy requires a more complex system for sample processing; however, it engages the advantages of improved mass accuracy and better sensitivity that derive from working with lower mass ions. Peptide maps from protein mixtures have been demonstrated to provide reliable identifications of microorganisms that are reasonably pure.…”
Section: Peptide Mapsmentioning
confidence: 99%
“…Peptide maps from protein mixtures have been demonstrated to provide reliable identifications of microorganisms that are reasonably pure. [79][80][81] As is the case with identifications based on protein molecular masses, it appears that the use of tryptic or other peptide masses as the basis for identification is extended with difficulty to mixtures of microorganisms. This reflects unpredictable suppression.…”
Section: Peptide Mapsmentioning
confidence: 99%
“…Proteins that have been extracted from microbial samples can be digested by enzymes; the sequence information of the peptides, obtained by MS/MS, can then be utilized to identify the proteins and deduce the microorganism's source through a proteome database search [23][24][25][26][27][28][29][30]. Recently, the authors' group reported approaches that use the selective proteotypic-peptide analysis (SPA) of protein digests that have been separated through CE to accurately identify bacterial mixtures [31][32][33].…”
mentioning
confidence: 99%